PERAN DEWAN WANITA PADA PENGUNGKAPAN ANTI PENYUAPAN DAN KINERJA KEUANGAN DI PERUSAHAAN SEKTOR PERTAMBANGAN DI BEI - yani zulvina; Desi Zulvina; Makhdalena Makhdalena; Fitri Zulvina (Jurnal Magister Akuntansi Trisakti, 2021)
This study aimed to examine the effect of Anti-Bribery Disclosure on Financial Performance and also to examine the role of the Women Board on Anti-Bribery Disclosure and Financial Performance where the Women Board is a moderating variable. This research was a quantitative research using 101 observation units from Mining Sector Companies listed on the Indonesia Stock Exchange during 2017-2019. This study used regression analysis techniques that were processed using the STATA version 14 application. The results showed that the Anti-Bribery Disclosure had no significant effect on financial performance as measured by ROA. The results also showed that the Women Board does not significantly moderate the relationship between Anti-Bribery Disclosure and Financial Performance. This research contributes to an increase in the assessment of company management that focuses on the gender of the company board and its role in achieving integrity and transparency of corporate activities in order to improve corporate sustainability.